2019
DOI: 10.1039/c8cc10239b
|View full text |Cite
|
Sign up to set email alerts
|

Metal-free desilylative C–C bond formation by visible-light photoredox catalysis

Abstract: A novel metal-free desilylative C–C bond formation from simple organosilanes by visible-light acridinium photoredox catalysis is presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…Molander et al, using ammonium silane catecholates 743 and the photoactivated 4CzIPN as oxidant, 236 showed that the liberated radicals add to imines 742 to afford benzylic amine products 744 (Scheme 202). On the other hand, Mancheño et al used benzyltrialkylsilanes as sources of benzyl radicals, but a strong oxidant, a mesitylacridinium salt was needed to liberate the radical in this case and the chemistry was limited to benzyl radicals, 237 while Bode et al liberated alkoxyakyl radicals from trimethylsilyloxy groups using triphenylpyrylium salts as photoredox reagents for cyclisation reactions in flow-based chemistry (not shown here). 238 Liberated alkyl radicals were also used 239 as precursors to acyl radicals 745 for addition to Michael acceptors yielding products 746.…”
Section: Cyanobenzene-derived Photocatalystsmentioning
confidence: 98%
“…Molander et al, using ammonium silane catecholates 743 and the photoactivated 4CzIPN as oxidant, 236 showed that the liberated radicals add to imines 742 to afford benzylic amine products 744 (Scheme 202). On the other hand, Mancheño et al used benzyltrialkylsilanes as sources of benzyl radicals, but a strong oxidant, a mesitylacridinium salt was needed to liberate the radical in this case and the chemistry was limited to benzyl radicals, 237 while Bode et al liberated alkoxyakyl radicals from trimethylsilyloxy groups using triphenylpyrylium salts as photoredox reagents for cyclisation reactions in flow-based chemistry (not shown here). 238 Liberated alkyl radicals were also used 239 as precursors to acyl radicals 745 for addition to Michael acceptors yielding products 746.…”
Section: Cyanobenzene-derived Photocatalystsmentioning
confidence: 98%
“…Silicon functional groups can be employed in cross-coupling reactions More recently, Mancheno and co-workers reported the use of silyl groups to access radical intermediates that underwent the Giese reaction with electrondeficient alkenes. [7] The key radical intermediate is generated following oxidation of the carbon-silicon bond via a singlet electron transfer process facilitated by an acridinium photocatalyst (Scheme 2).…”
Section: Introductionmentioning
confidence: 99%
“…The alkynylation reaction involving an alkynyl bromide gave 20 in fair yield, as did vinylation with the corresponding vinyl bromide to give 21 , which also demonstrated tolerance of the reaction toward a Boc protecting group. The cross-coupling permitted the installation of primary nonactivated alkyl groups including a butyl group ( 25 ), a (trimethylsilyl)methyl group without overoxidation ( 26 ), 20 or a 3-oxopropyl unit ( 27 ). Moderate to good yields were obtained with secondary alkyl chains, including tetrahydropyranyl ( 4 – 18 ), cyclohexyl ( 22 ), and sec -butyl ( 24 ) (Scheme 4 ).…”
Section: Synthesis Of the Martin Silicatesmentioning
confidence: 99%